The quantification of joint laxity in dancers and gymnasts - Gannon, L. M.; Bird, H. A. (Journal of Sports Sciences, 1999)
The aim of this study was to determine the range of movement in gymnastic and dance populations. Sixty-five participants (41 females, 24 males; mean age 21.4 years) were assessed. The sample included dancers and gymnasts ranging from novice and club standard to international and professional status. Non-specialized physical education students acted as controls. Range of movement was measured at the shoulders, hips, lumbar spine and ankles using a Loebl hydrogoniometer, and inherent joint laxity was assessed using Beighton and coworkers' adaptation of the Carter and Wilkinson 9-point scale. The right and left sides of the body were assessed and measures of active and passive motion were recorded. A graded increase in laxity was observed from controls, through novice gymnasts, to dancers and finally international gymnasts. The greater laxity of females than males was also confirmed. Dancers and gymnasts had a greater passive range of movement in all joints, which was partly inherited and partly acquired. There was a large difference between their active and passive ranges, which appeared to render the joints unstable.